Effect of Respiratory Training on Dysphagia in Children with Cerebral Palsy - Qishan LIU; Haofeng MO; Xiaofang CHEN (康复学报)
Objective:To observe the effect of respiratory training on dysphagia in children with cerebral palsy.Methods:A total of 96 eligible children with cerebral palsy accompanied by dysphagia were divided into observation group and control group according to the random number table method, with 48 cases in each group. The basic rehabilitation training was used in both groups. And the observation group was given breathing training in addition, 30 minutes per time, once a day, 5 days per week, 3 months as a course of treatment. The degree and grade of dysphagia were assessed by DDS before and after treatment, and the curative effect was assessed by Fujima Ichiro's dysphagia evaluation criteria before and after treatment.Results:There was no significant difference in DDS scores and dysphagia grade between the two groups before treatment(P>0.05).After three months of treatment, the DDS scores of two groups showed significant improvement compared with those before treatment(P<0.05).The total scores of DDS, oral and pharyngeal stages in the observation group were(5.33±3.08), (4.63±2.23), (0.70±0.78)respectively, which were better than those in the control group(7.20±3.43), (5.58±2.13), (1.81±1.38).The differences were statistically significant(P<0.05).The DDS score in oesophagus stage of the observation group was(0.06±0.24)and that of the control group was(0.08±0.28).There was no significant difference between the two groups(P>0.05).The DDS scores of children with spastic quadriplegia, involuntary motor type and mixed cerebral palsy before and after treatment in the two groups were significantly improved compared with those before treatment(P<0.05).The DDS scores of children with spastic quadriplegia, involuntary motor type and mixed cerebral palsy in the observation group(6.58±2.47), (4.57±2.10)and(4.57±2.59)were better than those in the control group(8.78±3.30), (6.41±2.35), (7.47±3.18), and there were significant differences between the two groups(P<0.05).There was no significant difference in the sample size of ataxia and spastic hemiplegia children(P>0.05).The degree of dysphagia was improved in the two groups before and after treatment, and the improvement in the observation group was more obvious than that in the control group(P<0.05).The total effective rate of the observation group(87.50%)was better than that of the control group(70.83%), and the difference was statistically significant(P<0.05).Conclusion:Respiratory training combined with basic swallowing training can significantly improve the symptoms of dysphagia in children with cerebral palsy.